10th Anniversary of Water - Hoekstra, Arjen Y. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
First issued in 2009, Water is celebrating our 10th anniversary this year. Thanks to all the dedicated researchers, reviewers, and editors, Water has become a popular outlet for cutting-edge research in the broad field of water science, technology, management, and governance. The open access format has proven to be attractive, and authors highly value the quick handling of papers, higher visibility and citations, as well as free and unlimited access to the new papers. After 10 years, Water has become an established journal in the field. This Special Issue is set up to mark the 10th anniversary of Water. It is devoted to the publication of comprehensive reviews encompassing the most significant developments in the realm of water sciences in the last decade.